Efficacy of Dorzagliatin and Related Factors in a Real-World Cohort of Type 2 Diabetes - Difei Lu; Rui Zheng; Na Li; Ying Gao (Journal of Diabetes Research)
Conclusions: Dorzagliatin is effective in lowering glucose levels in patients with T2D in a real-world setting. Patients with lower BMI, higher baseline HbA1c, and shorter duration of disease may be robust responders to dorzagliatin treatment.